Pendidikan dan Pelatihan Memoderasi Pengaruh Kemampuan Teknik Personal dan IT Sophistication pada Kinerja SIA - Utami, I Gusti Agung Pradnya; Widhiyani, Ni Luh Sari (E-Jurnal Akuntansi, 2021)
Implementation of AIS is indispensable for organizations as a means to support operational and administrative activities. This research aims to prove empirically the effect of ability personal techniques and IT sophistication with education and training as moderating variables on AIS performance. The population of this research is employees who use AIS at Dinas Perindustrian dan Perdagangan Provinsi Bali. The research sample was determined based on a non-probability sampling method with a saturated sample technique in order to obtain 84 civil servants who used AIS at Dinas Perindustrian dan Perdagangan Provinsi Bali. Data collection is done through questionnaire and interview. The analysis technique in this research is Moderated Regression Analysis (MRA). The result of analysis shows that education and training strengthen the effect of ability personal techniques and IT sophistication on AIS performance. Keywords: Ability Personal Techniques; IT Sophistication; Education and Training; AIS Performance.